1994
DOI: 10.1183/09031936.94.07101839
|View full text |Cite
|
Sign up to set email alerts
|

Lung deposition of budesonide from Turbuhaler is twice that from a pressurized metered-dose inhaler P-MDI

Abstract: L Lu un ng g d de ep po os si it ti io on n o of f b bu ud de es so on ni id de e f fr ro om m T Tu ur rb bu uh ha al le er r¤ ¤ i is s t tw wi ic ce e t th ha atABSTRACT: The pulmonary and systemic availability of budesonide after inhalation from a dry powder inhaler, Turbuhaler®, and from a pressurized metered-dose inhaler (P-MDI) were compared in healthy volunteers. Two different methods were used to assess pulmonary availability: 1) calculated from the systemic availability corrected for an oral availabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
167
2
66

Year Published

1995
1995
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 374 publications
(249 citation statements)
references
References 6 publications
14
167
2
66
Order By: Relevance
“…Hence, the fate within the lung of this fraction, which eventually determines the extent and duration of pharmacological activity, cannot be deduced from plasma determinations of MAT, as has been implied by some investigators [19]. The elimination half-life of budesonide was close to 5 h in the present study, which is longer than the 2±3 h found in earlier studies [2,10]. This discrepancy is likely due to shorter sampling times and a lower sensitivity in the Tables 4a and 4b Pharmacokinetic parameters derived from repeated dose inhalations (1000 mg twice daily) of budesonide via Turbuhaler and of uticasone via pMDI and Diskus.…”
Section: Discussioncontrasting
confidence: 38%
See 2 more Smart Citations
“…Hence, the fate within the lung of this fraction, which eventually determines the extent and duration of pharmacological activity, cannot be deduced from plasma determinations of MAT, as has been implied by some investigators [19]. The elimination half-life of budesonide was close to 5 h in the present study, which is longer than the 2±3 h found in earlier studies [2,10]. This discrepancy is likely due to shorter sampling times and a lower sensitivity in the Tables 4a and 4b Pharmacokinetic parameters derived from repeated dose inhalations (1000 mg twice daily) of budesonide via Turbuhaler and of uticasone via pMDI and Diskus.…”
Section: Discussioncontrasting
confidence: 38%
“…This discrepancy between single and repeated dosing for cortisol suppression may be explained by the pharmacokinetic properties of the drugs, since¯uticasone has been found to have a slower systemic elimination than budesonide, leading to accumulation and doubling of plasma concentrations after repeated dosing [3]. The elimination half-life of¯utica-sone is considerably longer than for many other inhaled corticosteroids; elimination half-lives in the range of 1.5±2.5 h have been reported for triamcinolone acetonide [8],¯unisolide [9], and budesonide [10]. Thus, an extensive distribution into tissues, as indicated by a high volume of distribution, appears to be the cause of this slow elimination of¯uticasone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a multiple dry-powder delivery system, the Turbuhaler, delivers approximately twice as much glucocorticoid to the lungs as other devices, but requires only half as large a dose. 60 …”
Section: Effect Of the Delivery Systemmentioning
confidence: 99%
“…Turbuhaler® has been thoroughly investigated with respect to lung deposition, and the general picture is that about 20-30% of the dose reaches the lung, both in healthy volunteers and in patients, at an inhalation flow of approximately 60 L·min -1 [41,47,51,52,57,67,68]. At a low inhalation flow, approximately 30 L·min -1 , lung deposition was lower than at a flow of 60 L·min -1 , but similar to that after a well-performed inhalation from the corresponding pMDI.…”
Section: Dry Powder Inhalersmentioning
confidence: 99%